2015
DOI: 10.3923/ajbs.2015.57.71
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Shoot Multiplication from Nodal Explants of Coccinia grandis (L.) Voigt. and It’s Antidiabetic and Antioxidant Activity

Abstract: Coccinia grandis (L.) Voigt. (Cucurbitaceae) is an important vegetable with high food and medicinal value. In this plant major problem is seed germination, seed setting and less number of fruit settings. Plant tissue culture technology may help to overcome these problems to a great extent. Therefore, the present study has been designed to develop an efficient protocol for in vitro shoot multiplication, as well as to check its antidiabetic and antioxidant activity. The nodal segments used as explants for cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Also, the biological and protective effect of the aqueous extract of dragon fruit (H. undatus) (kg/mg 500) showed a significant increase in its weight (3.36650 ± 332 g ), P<0.05 when compared with the positive control group (2.67603 ± 200.833g), and this may be because these doses of plant extract may effect on sensory perception, and then effect on appetite ( a, b, c, and d) refer to the significant differences at P<0.05; Different letters (a, b, c, and d) refer to the non-significant differences at P<0.05); FCA: Freund's Complete Adjuvant Table 1. Showing relative weights of the rats for the four groups al., 2020), and dragon fruits H. undatus extract is a good source of polyphenols that have antioxidant properties (Hernández and Salazar, 2012); And that the pulp and peel of this fruit have many chemical compounds that possess antimicrobial activity that can be used as a natural antioxidant (Patel and Ishnava, 2019), as well as containing many vitamins and minerals which have a significant effect on the body health (Hossain et al, 2021). The protective effect of Gallic acid showed a significant increase in its weight at the probability level (P<0.05) (3.51584 ± 284.1667 g) when compared with the positive control (2.67603 ± 200.833 g) of the body (Reckziegel et al, 2016) By influencing the two hormones responsible for feeling full and improving insulin resistance, leptin and adiponectin (Hsu and Yen, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the biological and protective effect of the aqueous extract of dragon fruit (H. undatus) (kg/mg 500) showed a significant increase in its weight (3.36650 ± 332 g ), P<0.05 when compared with the positive control group (2.67603 ± 200.833g), and this may be because these doses of plant extract may effect on sensory perception, and then effect on appetite ( a, b, c, and d) refer to the significant differences at P<0.05; Different letters (a, b, c, and d) refer to the non-significant differences at P<0.05); FCA: Freund's Complete Adjuvant Table 1. Showing relative weights of the rats for the four groups al., 2020), and dragon fruits H. undatus extract is a good source of polyphenols that have antioxidant properties (Hernández and Salazar, 2012); And that the pulp and peel of this fruit have many chemical compounds that possess antimicrobial activity that can be used as a natural antioxidant (Patel and Ishnava, 2019), as well as containing many vitamins and minerals which have a significant effect on the body health (Hossain et al, 2021). The protective effect of Gallic acid showed a significant increase in its weight at the probability level (P<0.05) (3.51584 ± 284.1667 g) when compared with the positive control (2.67603 ± 200.833 g) of the body (Reckziegel et al, 2016) By influencing the two hormones responsible for feeling full and improving insulin resistance, leptin and adiponectin (Hsu and Yen, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Dragon fruit is regarded as the "Powerhouse of Nutrition" among all fruits. Due to its low calorie, cholesterol-free, and antioxidant content, it reduces heart disease risk and keeps blood pressure stable (Patel & Ishnava, 2019). Betalains have the potential to decrease cancer cells and can fight oxidative stress.…”
Section: Determination Of Possibilities Of Dragon Fruit Cultivationmentioning
confidence: 99%
“…The fruit extract of C. grandis obtained by various methods of extraction, i.e., decoction, alcohol maceration, water maceration, and Soxhlet extraction, showed inhibition of α-glucosidase activity (Alagar et al, 2014). The methanol extract of C. grandis fruits, callus, and different combination mixtures of callus at a concentration of 1.0 mg/l inhibited α-amylase enzymatic activity with inhibition percentages of 54.29%, 75.72%, and 80.00%, respectively (Patel and Ishnava, 2015). Pulbutr et al (2017) revealed that the aqueous extract of leaves and stems of C. grandis significantly inhibited α-amylase activity with IC 50 of 8.09 ± 0.72 and 8.06 ± 1.27 mg/ml, respectively.…”
Section: Inhibition Of Digestive Enzymesmentioning
confidence: 99%